The roles of vitamin D and polyphenols in the management of age-related macular degeneration: a narrative review - Fernandes, Nádia (2023)
Age-related macular degeneration (AMD) is a chronic progressive ocular disease and the main cause of severe visual impairment in the elderly. Vitamin D deficiency may be a risk factor for AMD. Additionally, current evidence suggests dietary advice of increasing the consumption of polyphenols, which may have antioxidant and anti-inflammatory properties. The aim of this review was to describe the roles of vitamin D levels and polyphenols in the management of AMD. The results of this review showed mixed evidence regarding the protective effect of vitamin D against AMD. Polyphenols (flavonoids group, curcumin, and resveratrol) seem to play an important role as angiogenesis inhibitors, but their effect on AMD is still unclear. Vitamin D and polyphenols may both play an important role as nutritional modifiable protective factors that reduce the risk of AMD progression. However, more research is necessary to better understand the roles of vitamin D and polyphenols in different stages of the disease.